PENGGUNAAN REGISTER DALAM APLIKASI TRANSPORTASI ONLINE DI SULAWESI UTARA - ., Natanael; Pelealu, Hetty; Ranuntu, Garryn Ch. (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2021)
ABSTRACT     This research entitled ‘Register Used in Online Transportation Application in North Sulawesi’. It is expected to give contribution for the theoretical building of the linguistic field, particularly supports the development of subject dealing with sociolinguistics for the other studies and especially also for the user of online transportation application as this research about the register used in online transportation application in North Sulawesi. It is an attempt to identify and classify the registers used in online transportation application and to analyze the variation of language and linguistic form of register used in online transportation application in North Sulawesi. The theories which used in this research are Martin Joos (1968) about variation of language and George Yule (2006) about linguistic form and this research applies a descriptive method. Datas were taken in Grab and Gojek applications menus, notifications, messages and services from December 2016 to July 2019 by the writer because he is also working as a Driver in both companies as well. The results of the analysis showed that there are 40 words which contain the variation of languages and linguistic form of register. Variation of languages that used in register word in online transportation application are frozen, formal, consultative, casual and intimate, while language form of register found in online transportation application are coinage, borrowing, compounding, blending, clipping, backformation, conversion and acronyms. The linguistic meanings of register are found using an online dictionary.Keywords : Register, Online Transportation Application : aSociolinguistic Analysis